Synthesis, mechanical characterization and photon radiation shielding properties of ZnO-Al2O3-Bi2O3-B2O3 glass system - Mohd Zaid, Mohd Hafiz; Matori, Khamirul Amin; Nazrin, S. N.; Azlan, M. N.; Hisam, R.; Iskandar, S. M.; Yusof, N. N.; Hila, F. C.; Sayyed, M. I. (Elsevier BV, 2021)
Novel zinc alumina bismuth borate glass system was fabricated according to the empirical formula x(ZnO)–5(Al2O3)–30(BiO3)–65-x(B2O3) with x = 0, 5, 10, 15, 20, 25 and 30 mol% using conventional glass melt-quenching technique. The structural, elastic and shielding properties of the ZnO–Al2O3–BiO3–B2O3 glasses were examined by X-ray diffraction (XRD), density, molar volume, ultrasonic velocities, and EPICS2017 simulation. The glass structure's amorphous phase was confirmed by XRD measurement. From the density measurement, the addition of ZnO will increase the density from 4.275 to 5.018 g/cm3 and the molar volume decreased from 44.479 to 38.595 cm3/mol. In addition, the OPD is decreased from 67.45 to 62.19 mol/cm3. The elastic properties approximated from measured shear (VS) and longitudinal (VL) ultrasonic velocities indicated that the decrease of B2O3 in glass network cause the rigidity of glasses increased from 2300 to 2621 m/s and 4082–4540 m/s when the ZnO content increased. Meanwhile, the longitudinal (L), shear (G), bulk (K) and Young's (E) modulus increased from 71.23 to 103.43 GPa, 22.61–34.47 GPa, 41.08–57.47 GPa and 57.29 and 86.18 GPa. Besides, Poisson's ratio decreased from 0.267 to 0.250 and micro hardness increased from 3.51 to 5.75 GPa. The EPICS2017 simulation program is used to determine the radiation shielding of the glasses. The results show a very interesting results where the replacement of B2O3 by ZnO causes an improvement of the attenuation competence for the glasses.